Human Blood Circular System Educational Digital Comics for Improving Learning Outcomes - Ananda Aisyah; Deni Setiawan (Jurnal Penelitian Pendidikan IPA, 2023)
The learning outcomes of class V at SDN Bendungan Semarang in science subjects on the human circulatory system are low. The average learning outcome of fifth-grade students at SDN Bendungan is 63, where the score is less than the standard of minimum value for science subjects, namely 75. This study aims to develop the learning media "Digital Comics for Education on the Human Circulatory System" as well as to test the design of media development, test the feasibility of media, as well as to find out the effectiveness of the learning media "Digital Comic Education for the Human Blood Circulation System." The method used in this study is the Research and Development method with the Borg and Gall development model. The subjects in this research and development were: (1) Grade V students at SDN Bendungan Semarang in the 2022/2023 school year with 28 students; (2) Class V teachers at SDN Bendungan; (3) experts, expert lecturers, or experts as testers of learning media and provide input to the learning media. Data collection techniques are questionnaires, interviews, documentation, observation, and tests. Data analysis used validity, reliability, normality, t-tests, and N-gain tests. Based on the study's results, suitable for use with a percentage of material experts' assessment of 86% and a percentage of media experts' assessment of 95%. The percentage of teacher responses is 91%, and the percentage of student responses is 89%. The t-test result is 0.000, so there is a significant difference between the pretest and the post-test results. The result of the N-gain test is 0.60957 in the medium criteria category. So that the results obtained are: (1) the design of learning media that is developed according to the needs of students and teachers in teaching and learning activities; (2) the assessment of media experts and material experts with very feasible criteria; (3) the use of effective learning media in increasing student effectiveness and motivation. Based on the responses of teachers and students, the results of the study show that learning media is appropriate for use in teaching and learning activities